Autophagic Flux Unleashes GATA4-NF-κB Axis to Promote Antioxidant Defense-Dependent Survival of Colorectal Cancer Cells under Chronic Acidosis. (26th December 2021) - Liu, Xiaojie; Zhao, Minnan; Sun, Xue; Meng, Zhenzhen; Bai, Xiaojing; Gong, Yanchao; Xu, Limei; Hao, Xiaohe; Yang, Tingting; Wei, Zhao; Zhang, Xiyu; Guo, Haiyang; et al.
Abstract : Solid tumors are usually associated with extracellular acidosis due to their increased dependence on glycolysis and poor vascularization. Cancer cells gradually become adapted to acidic microenvironment and even acquire increased aggressiveness. They are resistant to apoptosis but exhibit increased autophagy that is essential for their survival. We here show that NF- κ B, a master regulator of cellular responses to stress, is upregulated in colorectal cancer cells adapted to acidosis (CRC-AA). NF- κ B is more relied upon for survival in CRC-AA than in their parental cells and drives a robust antioxidant response. Supplementation of antioxidant abolishes the increased sensitivity of CRC-AA to NF- κ B inhibition or depletion, suggesting that NF- κ B supports the survival of CRC-AA by maintaining redox homeostasis. Because SQSTM1/p62 is known to mediate the selective autophagy of GATA4 that augments NF- κ B function, we tested whether the enhanced autophagic flux and consequently the reduction of SQSTM1/p62 in CRC-AA cells could activate the GATA4-NF- κ B axis. Indeed, GATA4 is upregulated in CRC-AA cells and augments the NF- κ B activity that underlies the increased expression of cytokines, inhibition of apoptosis, and reduction of reactive oxygen species. Interestingly, secretory factors derived from HCT15-AA cells, the soluble ICAM-1 in particular, also possess antioxidant cytoprotective effect against acidic stress. Together, our results demonstrate a prosurvival role of the p62-restricted GATA4-NF- κ B axis in cancer cells adapted to acidic microenvironment.